(untitled) (Journal of Hama University, 2024)
the aim of this research was to study the life cycle of pistachio bark beetle, Hylesinus vestitus, in the Salamiyah region, 30 km east of Hama city, during 2021-2022., and to identify the weak points in the life of this insect, in order to control it and reduce its damage. by monitoring its reproduction in pistachio woods that attract females, and collecting samples from the twigs of pistachio trees infected with this insect on a weekly basis and dissecting them to monitor the activity of adults. The results showed that the insect spends the estivation in the adult stage inside the feeding tunnels in the twigs of trees in the field. About two-thirds of its numbers continue to hibernate in these tunnels until the next spring, then they move to the weak or dead branches with the aim of breeding during March and April, while about a third of them move in Autumn to the weak or dead branches for reproduction and overwintering at the larval stage within the breeding tunnels that they bore under the bark. New adults emerging from the branches of the spring reproduction, causing subsequent infections during May and June, as they emerge from the branches during these two months. The results also showed that the insect in Salamiyah area has two overlapping generations in the first year, autumn and the second, spring. The first generation extends from the beginning of October until the end of April, while the second generation extends from the beginning of March to the end of June. Adults are present throught the year, and the incomplete stages disappear during July, August, September and most of October. These results help to determine the optimal date for hanging pistachio wood as traps to collect and dispose of females, as well as to determine the optimal date for controlling adults in the field using specialized pesticides.